2018
DOI: 10.1017/s1759078718000144
|View full text |Cite
|
Sign up to set email alerts
|

KIT coaxial gyrotron development: from ITER toward DEMO

Abstract: Karlsruhe Institute of Technology (KIT) is doing research and development in the field of megawatt-class radio frequency (RF) sources (gyrotrons) for the Electron Cyclotron Resonance Heating (ECRH) systems of the International Thermonuclear Experimental Reactor (ITER) and the DEMOnstration Fusion Power Plant that will follow ITER. In the focus is the development and verification of the European coaxial-cavity gyrotron technology which shall lead to gyrotrons operating at an RF output power significantly larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The next step for the coaxial gyrotron technology towards DEMO is to prove experimentally its capability for long-pulse operation, especially with respect to the cooling and alignment of the coaxial insert. To this end, the 170 GHz, 2 MW short-pulse coaxial gyrotron at KIT has been upgraded with new, water-cooled components [12][13]. In particular, the beam tunnel, cavity, quasi-optical system, and mirror box have now independent cooling systems.…”
Section: Coaxial Gyrotron Technology At Longer Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step for the coaxial gyrotron technology towards DEMO is to prove experimentally its capability for long-pulse operation, especially with respect to the cooling and alignment of the coaxial insert. To this end, the 170 GHz, 2 MW short-pulse coaxial gyrotron at KIT has been upgraded with new, water-cooled components [12][13]. In particular, the beam tunnel, cavity, quasi-optical system, and mirror box have now independent cooling systems.…”
Section: Coaxial Gyrotron Technology At Longer Pulsesmentioning
confidence: 99%
“…Following the short-pulse validation of the upgraded components using the diode short-pulse electron gun, the pulse length will be gradually increased the up to 100 ms. Two new advanced triode electron guns are planned to be used: The first is based on the technology of coated emitter edges ( [15], see paragraph 2.5 for more details) and the second is an Inverse Magnetron Injection Gun manufactured by KIT [12], [16].…”
Section: Coaxial Gyrotron Technology At Longer Pulsesmentioning
confidence: 99%
“…The nominal operating parameters of the KIT 170 GHz, 2 MW coaxial-cavity pre-prototype are summarized in Table 1 [1]. As a first step towards a long-pulse/CW gyrotron, the modular gyrotron prototype was refurbished by introducing cooling systems for the beam tunnel, cavity, quasi-optical system, output CVD diamond window and collector [2]. The goal of this first step is to achieve a pulse length up to 100 ms.…”
Section: Modular 170 Ghz 2 Mw Coaxial Cavity Gyrotronmentioning
confidence: 99%
“…In Fig. 3 the coaxial-cavity long-pulse gyrotron [3] is shown in the superconducting magnet (SCM). The measurements and analysis of the RF signal has shown that the gyrotron is operating absolutely stable at a single frequency and therefore in only one cavity mode.…”
Section: Experimental Verification Of the Long-pulse Coaxial Cavity Gmentioning
confidence: 99%
“…However, it has to be proven that the coaxial-cavity technology can be used in steady-state operation. That shall be achieved by upgrading the existing 2 MW 170 GHz short-pulse prototype with a cooling system and the implementation of advanced Magnetron Injection Guns (MIGs) [3]. Both, the advanced MIGs as well as the longpulse gyrotron will show the way towards a possible solution for DEMO with a significantly higher output power at higher operating frequencies.…”
Section: Introductionmentioning
confidence: 99%